(untitled) (Texas Journal of Medical Science, 2025)
Undifferentiated connective tissue dysplasia (UCTD) is a genetically determined condition characterized by systemic manifestations affecting multiple organs, including the cardiovascular system. Children and adolescents with UCTD demonstrate impaired structural, functional, and autonomic regulation of cardiac activity, which reduces their tolerance to physical stress.